The Use of Hydroponic Growth Systems to Study the Root and Shoot Ionome of Arabidopsis thaliana - Berezin, Irina; Elazar, Meirav; Gaash, Rachel; Avramov-Mor, Meital; Shaul, Orit (IntechOpen, 2012)
None